Clinical Factors Associated with Progression to AIDS in the Italian Cohort of HIV-Positive Hemophiliacs - Schinaia, N; Ghirardini, A M G; Mazzucconi, M G; Tagariello, G; Morfini, M; Chiarotti, F; the G.I.C.C (Thrombosis and Haemostasis, 1994)
This study updates estimates of the cumulative incidence of AIDS among Italian patients with congenital coagulation disorders (mostly hemophiliacs), and elucidates the role of age at seroconversion, type and amount of replacement therapy, and HBV co-infection in progression. Information was collected both retrospectively and prospectively on 767 HIV-1 positive patients enrolled in the on-going national registry of patients with congenital coagulation disorders. The seroconversion date was estimated as the median point of each patient’s seroconversion interval, under a Weibull distribution applied to the overall interval. The independence of factors associated to faster progression was assessed by multivariate analysis. The cumulative incidence of AIDS was estimated using the Kaplan-Meier survival analysis at 17.0% (95% Cl = 14.1-19.9%) over an 8-year period for Italian hemophiliacs. Patients with age greater than or equal to 35 years exhibited the highest cumulative incidence of AIDS over the same time period, 32.5% (95% Cl = 22.2-42.8%). Factor IX recipients (i.e. severe B hemophiliacs) had higher cumulative incidence of AIDS (23.3% vs 14.2%, p = 0.01) than factor VIII recipients (i.e. severe A hemophiliacs), as did severe A hemophiliacs on less-than-20,000 IU/yearly of plasma-derived clotting factor concentrates, as opposed to A hemophiliacs using an average of more than 20,000 IU (18.8% vs 10.9%, p = 0.02). No statistically significant difference in progression was observed between HBsAg-positive vs HBsAg-negative hemophiliacs (10.5% vs 16.4%, p = 0.10). Virological, immunological or both reasons can account for such findings, and should be investigated from the laboratory standpoint.